Reduction in thermal conductivity of monolayer MoS2 by large mechanical strains for efficient thermal management - Jun Liu; Mengqi Fang; Eui-Hyeok Yang; Xian Zhang (Scientific Reports)
Abstract Two-dimensional (2D) materials such as graphene and transition metal dichalcogenides (TMDC) have received extensive research interests and investigations in the past decade. In this research, we report the first experimental measurement of the in-plane thermal conductivity of MoS2 monolayer under a large mechanical strain using optothermal Raman technique. This measurement technique is direct without additional processing to the material, and MoS2’s absorption coefficient is discovered during the measurement process to further increase this technique’s precision. Tunable uniaxial tensile strains are applied on the MoS2 monolayer by stretching a flexible substrate it sits on. Experimental results demonstrate that, the thermal conductivity is substantially suppressed by tensile strains: under the tensile strain of 6.3%, the thermal conductivity of the MoS2 monolayer drops approximately by 62%. A serious of thermal transport properties at a group of mechanical strains are also reported, presenting a strain-dependent trend. It is the first and original study of 2D materials’ thermal transport properties under a large mechanical strain (> 1%), and provides important information that the thermal transport of MoS2 will significantly decrease at a large mechanical strain. This finding provides the key information for flexible and wearable electronics thermal management and designs.